Tradisi Madeung Dalam Perawatan Ibu Nifas Pada Masyarakat Aceh (Studi Literatur Review) - Rachmawati, Windi Chusniah; Mulmaijah, An Nur Ghamiyyu; Pramudya, Dandy Arie; Mahardika, Grace Widya Dharma; Maulida, Marshanda Rachma; Dwiastuty, Nabilla Putri Wahyu (Universitas Negeri Malang, 2024)
Aceh is a region that has unique culture and traditions, the Madeung tradition is a traditional healing tradition that is commonly practiced in Aceh. This treatment is usually given to mothers during the postpartum period to help improve organ recovery during the postpartum period. Madeung is usually performed by midwives on their patients without thinking about the side effects of the Madeung tradition. Mothers during the postpartum period have a high risk of death, recorded in every thousand live births per year. One sign of the success of the (SDGs) is reducing maternal mortality. The aim of this research is to analyze various things related to the Madeung tradition for postpartum mothers in Aceh. This research was conducted using the literature review method on related journal articles accessed on Google Scholar. Based on this article, it was found that there are many Acehnese people who still practice the Madeung tradition. There are several factors that influence this, including employment factors, level of education and knowledge.